Faktor Determinan Pengembangan Karakter Peduli Lingkungan Berbasis Sekolah Inklusi - abdul basit (Jurnal Rontal Keilmuan Pancasila dan Kewarganegaraan, 2020)
This research aims to picture the determinant factors of Environmental Awareness Character through Adiwiyata program. The program belongs to a priority program implemented by SMK Negeri 3 Probolinggo. The program itself has purpose to improve the school quality and in line with the realization towards an adiwiyata independent goal. The research is carried using qualitative approach where data is collected through structural in depth interview, observation and documentation. The key informants involved group of pupils where disabilities student and regular students are grouped. The research findings include the key determinant is observed within a relatively low interaction between teachers and students at school. This is caused by online learning carried and implemented during the pandemic. However, school has implemented a policy to allow students to carry a practices to improve their capabilities to meet industrial need. Students are allowed to attend class in group of 8 pupils based on vocation by complying health protocol to prevent the virus outbreak. Covid-19 has caused unprecedented impact to pupils where students are urged to record their learning in a video. This is needed to ensure pupils follow environmental awareness during their learn from home. Thus, activities repeated from home would create a custom among students with disabilities and regular students to maintain the environmental awareness in order to realize the green living that would impact to the rest of the community, individual character, neighborhood, and society.